Study of Clinical Profile and outcome of Traumatic brain injury - KC, Raj Kumar; Khambu, Ashok; Shrestha, Ram Chandra; Thapa, Divas; Gyawali, Nishchal (Nepal Journal of Neuroscience, 2025)
Introduction: Traumatic Brain Injury (TBI) is a major cause of death and disability globally affecting millions of people each year. The clinical presentation and prognosis of TBI vary widely, depending on factors such as the severity of the injury, the location of brain damage and patient’s overall health. This study is aimed for learning the clinical profile and outcome of traumatic brain injuries in our setting. Materials and Methods: This is a hospital based observational descriptive cross-sectional study conducted for a period of 18 month at Neurosurgical unit of Universal College of medical science teaching hospital, Bhairahawa. All the patients presenting in the Emergency department with TBI were enrolled in the study. Results: There were total 278 cases mostly male (76.6%) and of age group 21 to 40 yrs. Most cases were mild head injury (60 %) and 48 cases (18.2%) had some pupillary abnormalities. The most common mode of injuries were RTA followed by fall injuries and physical assault. Most of the cases underwent conservative management and 44 cases (15.8%) had undergone surgeries. Outcome of TBI at discharge in terms of GOS was 1.88 for severe TBI, 4.67 for moderate TBI and 5 for mild TBI. Mean GOS after 3 months follow up was 5 for mild, 5 for moderate TBI and 3.69 for severe TBI. Conclusion: The study provides insightful data on patients with head injuries, revealing several key trends. Functional outcome of severe head injuries according to GOS was poor at time of discharge but improved after 3 months.